Hyperton vätskebehandling av kor med högersidig löpmagsdislokation - Bergström, Sara (2005)
The aim of this study was to investigate the effects of an infusion of hypertonic saline solution (HSS) in combination with an oral waterload on cows suffering from rightsided displacement of the abomasum (RDA). Six dairy cows were treated with 7,2% HSS in a dosis of 5 ml per kg bodyweight. They also received an oral waterload of approximately 15 liters. To monitor changes in fluid-, acid-base- and electrolyte-balance, bloodsamples were collected during the next 24 hours. During this period, the cows also underwent surgery to empty and correct the position of the abomasum. The majority of the cows were initially dehydrated, hypochloremic, hyponatremic and hypokalemic. Two were slightly alkalotic, one was acidotic and all of the cows suffered from hyperglycemia. The treatment resulted in an immediate expansion of plasmavolyme as well as an immediate reduction in blood-glucose-levels. A slight reduction in pH was also observed directly after the infusion. Twenty-four hours after the infusion the chloride, sodium and potassiumconcentrations were all near normal.